Design and Development of Solbag: An Innovative and Sustainable Learning Bag by Integration of Renewable Energy Technology - Lukma, Hazairin Nikmatul; Yuana, Haris (Research and Social Study Institute, 2025)
Background: Indonesia, as an equatorial country, has a large solar energy potential. The great intensity of solar radiation throughout the year makes solar panel technology an alternative source of electricity, particularly in rural locations that are not yet connected to the conventional grid.Aims: The aim of this research is to develop a prototype study bag that can utilize solar energy to charge portable electronic devices such as study lamps, using a simple electronic circuit but with stable power output. This integration of renewable energy technology can support educational activities based on environmental sustainability principles, particularly in remote areas.Methods: The research method includes the design, manufacturing and testing stages of the prototype, including empirical validity testing and theoretical validity testing by a team of experts.Result: The test results meet the theoretical validity interpretation criteria with a percentage of 93.67%, which is included in the very valid category, with a percentage of agreement value of 91.57%, which indicates the conformity of the assessment among the validators. In the empirical validity assessment, the Solbag system is able to provide an average stable voltage of 3.865 V. In addition, user analysis shows that Solbag is considered practical, functional, and contributes to increasing student awareness of the use of renewable energy.Conclusion: The solbag bag system fits within the optimal range based on prototypes and comparable goods related to portable solar study lamps, and possesses the ability to serve as an eco-friendly lighting solution for students in rural areas with limited energy access.